2021
DOI: 10.1007/s00277-020-04356-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with multiple myeloma participating in a multidisciplinary rehabilitation program

Abstract: AcknowledgementWe would like to thank all patients who participated in the study and the members of the Danish Myeloma Study Group for referring patients to the study. We are grateful for the help received from the entire clinical team at the Danish Knowledge Centre for Rehabilitation and Palliative Care (REHPA) and with special thanks to the project manager Jan Børge Tofte for taking lead on the residential stay. Finally, we also wish to thank two members with multiple myeloma from The Danish Myeloma Patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 60 publications
0
10
1
Order By: Relevance
“…In this study, worrying (a core symptom of MM patients with chemotherapy) had the most effect on other symptoms. A total of 54.1% of the participants in our study experienced worrying; this prevalence was higher than in previous studies [ 15 ]. According to the Symptom Experience Mould (SEM), personal and clinical characteristics have an effect on MM patients’ illness perception, and compared to non-chemotherapy patients, worrying includes not only worry about the disease, but also about the effectiveness of the chemotherapy and financial pressure [ 42 ].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In this study, worrying (a core symptom of MM patients with chemotherapy) had the most effect on other symptoms. A total of 54.1% of the participants in our study experienced worrying; this prevalence was higher than in previous studies [ 15 ]. According to the Symptom Experience Mould (SEM), personal and clinical characteristics have an effect on MM patients’ illness perception, and compared to non-chemotherapy patients, worrying includes not only worry about the disease, but also about the effectiveness of the chemotherapy and financial pressure [ 42 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, MM patients suffer from various psychological symptoms due to the combination of the disease and the adverse effects of chemotherapy. Indeed, approximately 25% of MM patients reportedly suffer from anxiety and depression [ 15 ]. Uncertainty is a common psychological problem due to a lack of information about fear of the disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effect of PT on health-related quality of life was not examined in this study. A recent previous study reported that there was no change in health-related quality of life before and after the 12-week multidisciplinary rehabilitation program in MM patients 17) . In the future, it is necessary to study more such cases and verify the safety and effectiveness of PT including health-related quality of life in patients with MM.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, MM patients suffer from psychological distress due to the combination of the disease and the adverse effects of chemotherapy. The study showed that one-quarter of MM patients experience the anxiety and depression (Nielsen et al, 2021).…”
Section: Backg Rou N Dmentioning
confidence: 99%